Legal Consequences For A Notary In Making An Authentic Deed Based On A Forged Letter - Christine, Christine; Djaja, Benny (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study aims to analyze the legal consequences for a notary in making an authentic deed based on a forged letter. This study used the literature study method and normative analysis to collect data from relevant literature sources. The results indicated that a notary involved in making an authentic deed based on a forged letter could face disciplinary sanctions, revocation of a notary's license, and criminal charges. In addition, they also face adverse social and reputational damage. A notary must maintain integrity, professionalism, and vigilance in every task carried out to prevent abuse or violations in making an authentic deed